Význam infekcie Helicobacterom pylori v etiológii bolestí brucha u detí - Cernák, A; Krajcírová, M; Cierna, I; Zaviacic, M; Simkovicová, M; Elánová, E; Bibza, J (Ceskoslovenska pediatrie, 1993)
Chronic and recurrent abdominal pain are frequent diagnostic problems in school age and adolescent children. The authors examined the IgG antibodies to Helicobacter pylori using ELISA in a group of 91 children. Positive results were found in 20 children, i.e. 22%. All children positive for Helicobacter pylori antibodies underwent an endoscopic examination with bioptic sampling of the gastric and duodenal mucosa. Bioptic samples were examined histologically and Helicobacter pylori was identified microscopically and using urease tests and cultivation. All 20 children with antibodies to Helicobacter pylori had histological evidence of chronic gastritis in the gastric antrum and infection with Helicobacter pylori was found in 16 cases. Detection of Helicobacter pylori IgG antibodies is useful in the selection of patients for endoscopic examination of the stomach and duodenum. Endoscopy is relevant also where antibodies to Helicobacter pylori are negative and the characteristic picture of chronic disease of the upper gastrointestinal tract is present.
Keywords: recidiva; Abdominal Pain; Humans; dítě; Child; Chronic Disease; protilátky bakteriální; ELISA; bolesti břicha; lidé; gastrointestinální nemoci; Enzyme-Linked Immunosorbent Assay; Antibodies, Bacterial; Helicobacter Infections; Helicobacter pylori; chronická nemoc; Adolescent; Recurrence; Gastrointestinal Diseases; infekce vyvolané Helicobacter pylori; mladiství